Reviews of new publications - Holmes, Derek A; Andrew, Paul (KUKILA, 1991)
Dekker, Rene W.R.J. 1990. Conservation and biology of megapodes (Megapodiidae, Galliformes, Aves). PhD Thesis, University of Amsterdam Silvius, MJ. & A.W. Tauflk. 1990. Conservation and land use of Pulau Kimaam, Irian Jaya. PHPA-AWB/Interwader Report Silvius, M.J. & M. Zieren. 1990. Three years of wetland and waterbird conservation activities in Indonesia, October 1987 -September 1990. PHPA-AWB. Erflemeijer, P., G.R. Alien & Zuwendra. 1989. Preliminary resource inventory of Bintuni Bay and recommendations for conservation and management. AWB-PHPA, Bogor. Gibb, David. 1990. Wallacea. A site guide for birdwatchers. Croxall, J.P. (Ed.). 1991. Seabird status and conservation: A supplement. ICBPTech. Publ. 11, Cambridge, IUCN(1990). 1990 IUCN Red list of threatened animals. IUCN, Gland, Switzerland and Cambridge, UK Holmes, D.A. & S.V. Nash. 1990. The birds of Sumatra and Kalimantan. Singapore: Oxford University Press